2017
DOI: 10.1038/s41598-017-05959-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of protein crowding within the nuclear pore complex in interphase and mitosis

Abstract: The central channel of the nuclear pore complex (NPC) is occupied by non-structured polypeptides with a high content of Phe-Gly (FG) motifs. This protein-rich environment functions as an entropic barrier that prevents the passage of molecules, as well as the binding sites for karyopherins, to regulate macromolecular traffic between the nucleoplasm and the cytoplasm. In this study, we expressed individual Nups fused with a crowding-sensitive probe (GimRET) to determine the spatial distribution of protein-rich d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…14 A recent study reported that FG-domains of Nup98 spontaneously self-assemble into particles in vitro at physiologic concentrations (≈10 µM). 6 This in vivo evidence suggests that even though FG-Nups self-assemble into protein-rich phases, several sets of Nups preferentially assemble into distinct protein-rich phases, possibly one at the cytoplasmic rim and another at the nucleoplasmic rim of the central channel. Another study using a crowding-sensitive fluorescent probe demonstrated that protein crowding is not homogeneous throughout the channel; "protein-rich" domains lie at both rims of the channel but not in the central cavity.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…14 A recent study reported that FG-domains of Nup98 spontaneously self-assemble into particles in vitro at physiologic concentrations (≈10 µM). 6 This in vivo evidence suggests that even though FG-Nups self-assemble into protein-rich phases, several sets of Nups preferentially assemble into distinct protein-rich phases, possibly one at the cytoplasmic rim and another at the nucleoplasmic rim of the central channel. Another study using a crowding-sensitive fluorescent probe demonstrated that protein crowding is not homogeneous throughout the channel; "protein-rich" domains lie at both rims of the channel but not in the central cavity.…”
Section: Introductionmentioning
confidence: 98%
“…6 Nups containing a large number of phenylalanine-glycine (FG) motifs (FG-Nups) in a long intrinsically disordered region (IDR-Nups) 7,8 form a molecular sieve-like environment that functions as a selective barrier with respect to molecular transport. 6 Nups containing a large number of phenylalanine-glycine (FG) motifs (FG-Nups) in a long intrinsically disordered region (IDR-Nups) 7,8 form a molecular sieve-like environment that functions as a selective barrier with respect to molecular transport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ELYS is crucial for NPC assembly because it recruits the Nup107-160 subcomplex to the chromatin where the NPC forms (Doucet & Hetzer, 2010;Franz et al, 2007). Kinetic analysis using live cell imaging of dividing cells showed that subcomplexes of the NPC are sequentially assembled on the chromatin to form a functional NPC (Anderson, Vargas, Hsiao, & Hetzer, 2009;Dultz et al, 2008;Konishi et al, 2016); the Nup107-160 subcomplex, and some fraction of Nup153, assembles in the earliest step of NPC assembly during telophase . In contrast, it has been suggested that the NPC is inserted into the sheetlike membrane generated from the ER cisternae during telophase (Lu, Ladinsky, & Kirchhausen, 2011).…”
mentioning
confidence: 99%